2023
DOI: 10.3389/fcvm.2023.1284826
|View full text |Cite
|
Sign up to set email alerts
|

Association between Parkinson's disease and the risk of adverse cardiovascular events: a systematic review and meta-analysis

Yan Hu,
Shanxia Xu

Abstract: BackgroundThis review aims to examine the association of Parkinson's disease (PD) with the increased risk of cardiovascular events.MethodsPubMed, Embase, CENTRAL, and Scopus databases were electronically searched for papers published up to 5 May 2023. Studies reporting the association between PD and the subsequent risks of stroke, myocardial infarction (MI), and cardiovascular mortality were included.ResultsSixteen studies were included in this review. The clinical data of 101,712 PD patients were compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…Additionally, we found that patients with a dual diagnosis of vitiligo and PD were found to experience a higher burden of cardiometabolic conditions. This accords with the elevated risk of cardiovascular and metabolic outcomes associated with the presence of PD (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 62%
“…Additionally, we found that patients with a dual diagnosis of vitiligo and PD were found to experience a higher burden of cardiometabolic conditions. This accords with the elevated risk of cardiovascular and metabolic outcomes associated with the presence of PD (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 62%
“…Epidemiological studies have suggested a possible relationship between the incidence of cardiocerebrovascular disease and PD, either as risk factors or as manifestations of PD itself [212,213]. Studies using Mendelian randomization method reveal that PD is correlated to high risk of coronary artery disease, stroke, ischemic stroke, and cardioembolic stroke compared with age-and gendermatched general population [214,215]. On the other hand, the deposition of aSyn in the brain of PD may be a potential pathogenic factor for cardiovascular disease and stroke [216].…”
Section: Cardiovascular Symptomsmentioning
confidence: 99%